Kajian Filosofis Konsep Epistemologi dan Aksiologi Pendidikan Islam - Rangga Sa'adillah SAP; Dewi Winarti; Daiyatul Khusnah (Universitas Nahdlatul Ulama Surabaya, 2021)
The terms of epistemology and axiology in education are endless discussions. The descriptions of epistemology and axiology regarding the concept and its relevance to Islamic education increasingly show views on the horizon of Islamic education. This article aims to elaborate the concepts of epistemology and axiology in the perspective of Islamic education. To describe the terms of epistemology and axiology in the perspective of Islamic education, the method used in this article is literature combined with annotated bibliography as a guide for annotating literature and analyzing discussion. This article produces several elaborative discussions including epistemology as a philosophical way to formulate knowledge, it can help us to develop new concepts in Islamic education such as bayani, burhani and irfani. Meanwhile, axiology as a philosophical guide to capture the existence of values ​​can be used to reaffirm the essence of basic values ​​in Islamic education.